2020
DOI: 10.1108/itp-05-2018-0256
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the role of intrinsic motivation in ISSP compliance: enterprise digital rights management system case

Abstract: PurposeEmployee compliance with information system security policies (ISSPs) has been emphasized as a key factor in protecting information assets against insider threats. Even though previous studies have identified extrinsic factors (in the form of external pressure, rewards and social norms) influencing employee compliance, the functioning of employees' intrinsic motivation has not been clearly analyzed. Thus, the aim of this study is to explore the influence of intrinsic motivations on employees' ISSP compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Second, this paper also extends our understanding of responsibility by dividing it into perceived causality and answerability as well as measuring them with self-developed instruments. Although multiple studies reported that responsibility has more than one dimension (Schlenker et al ., 1994; Auhagen and Bierhoff, 2002), responsibility has been widely treated as a broad and unidimensional concept empirically (Jeon et al ., 2021; Erlandsson et al ., 2015). To fill this gap, we developed instruments to empirically measure perceived causality and answerability by following a rigorous instrument development procedure (Moore and Benbasat, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Second, this paper also extends our understanding of responsibility by dividing it into perceived causality and answerability as well as measuring them with self-developed instruments. Although multiple studies reported that responsibility has more than one dimension (Schlenker et al ., 1994; Auhagen and Bierhoff, 2002), responsibility has been widely treated as a broad and unidimensional concept empirically (Jeon et al ., 2021; Erlandsson et al ., 2015). To fill this gap, we developed instruments to empirically measure perceived causality and answerability by following a rigorous instrument development procedure (Moore and Benbasat, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…proposed that the freedom and control offered to crowdworkers on task decisionmaking is a key determinant of their satisfaction. Jeon et al (2020) found that employees' perception of discretion in making decisions with regard to information systems security policies positively influences their self-efficacy and feelings of responsibility for security-related tasks. Similarly, Ke and Zhang (2010), Ke et al (2012), Menard et al (2017), and Liang et al (2015) also underlined the relevance of work-task autonomy.…”
Section: Job Autonomy In Crowdsourcing Platformsmentioning
confidence: 98%
“…Security-related subjective norms and security compliance pressure The human aspect of ISP compliance in organizations has been and continues to be an important area of academic research (Jeon et al, 2020;Kim and Han, 2019;Vedadi and Warkentin, 2020). The prior literature has used many theories to explain how and why employees comply with ISPs (Bulgurcu et al, 2010;Moody et al, 2018).…”
Section: Theoretical Backgroundmentioning
confidence: 99%